Implementing Video Recording to Improve the Content of Opening Speech: Menerapkan Perekaman Video untuk Meningkatkan Isi Pidato Pembukaan - Santoso , Dian Rahma (Universitas Muhammadiyah Sidoarjo, 2017)
This study investigated the implementation of video recording to improve the students’ ability in presenting opening speech which focused on the content delivery. A classroom action research was used to collect the data from three cycles, and observation. The result showed all students could meet the minimum requirement after doing the process of recording their performance for three cycles.It improved the content delivery significantly after looking at and evaluating the video of performance. Students not only could accomplish the clear purpose of the presentation by introducing the topic clearly, told the thesis statement and preview the points of the speech. Finally, video recording also improved the students’ performance such as movement of gestures and body language, and the eye contact.